Jurisprudential - Legal analysis of interference of injuries With emphasizing the Islamic Penal Code 2013 - hasan moradi (Faṣlnāmah-i Pizhūhish-i Huqūq-i Kiyfarī, 2020)
Standardization of multiplicity of injuries for how to get a retaliation or compensation has been a significant part of the jurisprudential doctrines about rules of Qisas. Contrary to the rule of multiplicity of crime which is one of the factors of aggravation of punishment, multiplicity of injuries has various assumptions: Sometimes a injury may be committed by one person against another person or others or by a few people against a person. It may also result from a blow or multiple blows, at a time or at different times. The jurists of the Imamieh religion have expressed different opinions in this regard. Some of them believe in interfering absolutely, Some of them believe in not-interfering absolutely, and Some of them, have a different opinion depending on the unit or multiple and consecutive or alternate blows. In the Islamic Penal Code, with the following the famous opinion in Imamieh jurisprudence and by accepting the not-interfering opinion, except in exceptional cases, provided that the multiple intentional injuries result in a multiplicity of retaliation. In this article, by analyzing the related jurisprudential doctrines, the criteria set out in the above mentioned law have been criticized and proposals for amending the law are provided.